2009
DOI: 10.1093/bja/aep178
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative use of dexmedetomidine in an infant with familial dysautonomia

Abstract: We present a case of a 10-month-old girl with familial dysautonomia, who was scheduled for the insertion of a gastrotomy tube via laparoscopy under general anaesthesia. We used a total i.v. anaesthetic technique including dexmedetomidine and titrated the drug to patients' haemodynamic status and BIS value. Vital signs remained virtually unchanged during the entire procedure, and the tracheal tube was removed at the end of the procedure. Postoperative course was uneventful. Careful planning of the anaesthetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…This selective agonist acts on α2 adrenoreceptors in the brain and spinal cord to inhibit sympathetic outflow, resulting in hypotension, bradycardia, sedation, analgesia, reduced salivation, and decreased bowel motility. 16 …”
Section: Cardiovascular Treatmentsmentioning
confidence: 99%
“…This selective agonist acts on α2 adrenoreceptors in the brain and spinal cord to inhibit sympathetic outflow, resulting in hypotension, bradycardia, sedation, analgesia, reduced salivation, and decreased bowel motility. 16 …”
Section: Cardiovascular Treatmentsmentioning
confidence: 99%
“…Until our research, evidence for the use of dexmedetomidine in FD was limited to anecdotal cases for intraoperative administration and concurrently used with sedatives, muscle relaxants, and analgesic medications [1, 10, 13]. DiGiusto et al reported a 28-year-old woman with FD who, after a jejunostomy tube replacement, developed severe agitation, hypertension, tachycardia, and diaphoresis consistent with adrenergic crisis [3].…”
Section: Discussionmentioning
confidence: 99%
“…These are often referred to as “dysautonomic” or “adrenergic crises”. Adrenergic crises are a consequence of the inability to restrain sympathetic overflow caused by congenital damage to the afferent nerves carrying baroreceptor inputs to the central nervous system [1, 3, 7, 14, 23, 24]. Adrenergic crises can be triggered by a variety of situations ranging from surgery and severe illness to daily emotions and feeding [6, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Olgularda entübasyon evresinde, ekstübasyon evresinde ve postoperatif dönemde istenmeyen bir hemodinamik dalgalanma yaşa-mamışlardır.…”
unclassified